2009
DOI: 10.3386/w15280
|View full text |Cite
|
Sign up to set email alerts
|

Spring Cleaning: Rural Water Impacts, Valuation and Property Rights Institutions

Abstract: In many societies, social norms create common property rights in natural resources, limiting incentives for private investment. This paper uses a randomized evaluation in Kenya to measure the health impacts of investments to improve source water quality through spring protection, estimate the value that households place on spring protection, and simulate the welfare impacts of alternative water property rights norms and institutions, including common property, freehold private property, and alternative "Lockea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(173 citation statements)
references
References 27 publications
5
167
1
Order By: Relevance
“…A third evaluation reported indirect evidence for contamination of piped water -the evaluation found at best an insignificant impact on diarrhoea morbidity for piped water supplied at source, noting that only one-quarter of households had reported boiling their water before drinking (Khanna 2008). In an evaluation of source water protection, Kremer et al (2009) find substantially higher pathogen content in household water compared to source water, arguing that the recontamination is 'due both to households' collection of water from multiple water sources and to partial recontamination of water in transport and storage' (p. 2). They suggest, however, that the reduced contamination by one-quarter in home water remained sufficient to account for the estimated 25 per cent reduction in child diarrhoea.…”
Section: Behaviour Changementioning
confidence: 97%
See 1 more Smart Citation
“…A third evaluation reported indirect evidence for contamination of piped water -the evaluation found at best an insignificant impact on diarrhoea morbidity for piped water supplied at source, noting that only one-quarter of households had reported boiling their water before drinking (Khanna 2008). In an evaluation of source water protection, Kremer et al (2009) find substantially higher pathogen content in household water compared to source water, arguing that the recontamination is 'due both to households' collection of water from multiple water sources and to partial recontamination of water in transport and storage' (p. 2). They suggest, however, that the reduced contamination by one-quarter in home water remained sufficient to account for the estimated 25 per cent reduction in child diarrhoea.…”
Section: Behaviour Changementioning
confidence: 97%
“…A number of studies comment on the issue of sustainability, but the extent to which studies include a formal evaluation of sustainability over time and in scale-up is limited. Our review identified only five follow-up evaluations conducted more than one year after the initial intervention had ended which assessed sustainability in reducing diarrhoea morbidity (Wilson and Chandler 1993, Hoque et al 1996, Brown et al 2007, deWilde et al 2008, Kremer et al 2009), in addition to one evaluation assessing compliance of two interventions six months and one year after they had ended ) and one assessing compliance four years later (Iijima et al 2001).…”
Section: Sustainabilitymentioning
confidence: 98%
“…There are some interventions that specifically target hand-dug wells and springs, most notably spring and well upgrading programmes (Kremer, Leino, Miguel, & Zwane, 2011;Philip & Stevens, 2013). Given the growing policy emphasis on reducing inequalities relating to water and sanitation, an important question is the extent to which such interventions can be considered pro-poor and how the incidence of benefits from well upgrading might vary across different socio-economic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Second, an efficient rights trading arrangement may be immiserating if instituted at the wrong stage of a region's development. Kremer et al (2011), studying Kenyan water purification systems, found demand for clean water to be highly income elastic. Thus, at very low incomes, a commons structure-where few water sources were protected from contamination-appears to be utility maximizing; at higher income levels consumers would be better off under a market based water management scheme-where water is more expensive but safer.…”
Section: Public Policy and Future Workmentioning
confidence: 99%